A D.H. Lawrence Chronology - Preston, P. author. aut Link
XXI, 208 p.
Keywords: 'Peter Preston has written and made thoroughly accessible to its readers a book which no-one working on Lawrence can now afford to have far from their work-table. How ever did we live without it? It has become, at a stroke, indispensable.' - John Worthen, D H Lawrence Society's Newsletter 'It creates a most absorbing chronological sequence out of materials brought together from an extremely wide variety of sources, in a very effective and professional way.' - Nicola Ceramella This volume traces the progress of Lawrence's life from its beginnings in the English Midlands through his world-wide travelling until his death in 1930. Details of the composition of his works in many forms and of the controversies that often followed their publication are included. Drawing on information from recent scholarly editions of his letters and works, it also offers details of his wide reading, and his relationships with figures as varied as E.M. Forster, Bertrand Russell, Katherine Mansfield, Lady Ottoline Morell and Aldous Huxley.